Multimodality and the construction of fear in Tatsuki Fujimoto's Chainsaw Man - Satriyo, Aria Maulana (ppjbsip, 2023)
The purpose of this study is to demonstrate the visual aspects featured in the Chainsaw Man manga, as well as how the modes depicted in the manga portray fear in the shape of Devils. The data for this study will come from Tatsuki Fujimoto's Chainsaw Man series, and it will be analysed using Multimodality Discourse Analysis and the Visual Grammar Design theory. The findings of this study show that the visual features of the Chainsaw Man manga include representational, compositional, and interactive aspects that assist to establish the narrative, the reader's sense of involvement, and how the represented participants are portrayed. Other visual and linguistic aspects, such as the story from the manga itself and the physical features and attributes of the Devil for example weaponry, aid in depicting the characterisation of fear through the Devil portrayed.